The Effect of Perceived Usefulness, Trust, and Privacy Concern on Purchase Decisions through Voice Marketing in Food Delivery Services: Evidence from Semarang, Indonesia - Sofyan Muaziz (Universal Business and Management Review, 2026)
The rapid advancement of artificial intelligence and natural language processing technologies has given rise to voice marketing as an emerging frontier in digital commerce, particularly within food delivery ecosystems. Despite the projected exponential growth of voice commerce globally, adoption rates in Indonesia remain disproportionately low, highlighting a critical research gap that demands empirical investigation. This study examines the simultaneous effects of perceived usefulness, trust, and privacy concern on purchase decisions through voice marketing among food delivery service users in Semarang, Indonesia—one of the country's fastest-growing metropolitan cities. Employing a quantitative explanatory design, data were collected via structured online questionnaires distributed to 386 respondents selected through purposive sampling. Multiple linear regression analysis using IBM SPSS Statistics version 27 was employed, complemented by validity, reliability, and classical assumption tests. Results demonstrate that perceived usefulness (β = 0.398; t = 12.546; p < 0.001), trust (β = 0.485; t = 15.299; p < 0.001), and privacy concern (β = 0.376; t = 11.856; p < 0.001) each exert a positive and statistically significant effect on purchase decisions. Collectively, the three variables account for 62.1% of the variance in purchase decisions (R² = 0.621; F = 208.814; p < 0.001). Trust emerges as the most dominant predictor, surpassing perceived usefulness—a finding that challenges the conventional hierarchy within the Technology Acceptance Model (TAM) and suggests the need for a trust-augmented TAM framework in voice commerce contexts. Notably, the positive effect of privacy concern reveals a privacy paradox phenomenon among Indonesian digital consumers, where perceived privacy risks do not inhibit—and may even reinforce—purchasing behavior through voice interfaces. These findings contribute to TAM literature, trust theory, and privacy concern scholarship, while offering evidence-based strategic implications for food delivery platforms, voice assistant developers, and digital policymakers operating in emerging markets. Keywords: voice marketing; perceived usefulness; trust; privacy concern; purchase decision; food delivery; Technology Acceptance Model; Indonesia